Cloning and Analysis of the Capsid Morphogenesis Genes of Pseudomonas aeruginosa Bacteriophage D3: Another Example of Protein Chain Mail? - Gilakjan, Zeynab A. (American Society for Microbiology, 1999)
The terminal DNA restriction fragments (PstI-D and -B) of Pseudomonas aeruginosa bacteriophage D3 were ligated, cloned, and sequenced. Of the nine open reading frames in this 8.3-kb fragment, four were identified as encoding large-subunit terminase, portal, ClpP protease, and major head proteins. The portal and capsid proteins showed significant homology with proteins of the lambdoid coliphage HK97. Phage D3 was purified by CsCl equilibrium gradient centrifugation (ρ = 1.533 g/ml), and sodium dodecyl sulfate-polyacrylamide gel electrophoresis revealed six proteins with molecular masses of 186, 91, 79, 70, 45, and 32 kDa. The pattern was unusual, since a major band corresponding to the expected head protein (43 kDa) was missing and a significant amount of the protein was retained in the stacking gel. The amino terminus of the 186-kDa protein was sequenced, revealing that the D3 head is composed of cross-linked 31-kDa protein subunits, resulting from the proteolysis of the 43-kDa precursor. This is identical to the situation observed with coliphage HK97.